STABILITY AND MICROBIOLOGICAL ANALYSIS OF ALOE BARBADENSIS AND CHAMOMILLA MATRICARIA PHARMACEUTICAL FORMS - Olimpia Dumitriu Buzia; Con Madalina; Alin Laurentiu Tatu; Denisa Marin Batir; Carmen Tiutiuca; Grigore Ionuta; Gabi Topor; Sergiu Focșăneanu; Mihaela Iamandii; Ovidiu Schipor; Alina Mihaela Calin (Romanian Society of Oral Rehabilitation, 2022)
In the present paper, we aimed to make two pharmaceutical forms ointment and gel, in the composition of which to be incorporated active substances with strong anti-acne and healing actions on skin lesions. The two forms, ointment and gel contain lyophilized extracts of Aloe barbandensis and Matricaria chamomilla, in the form of alcoholic extract, as well as other active substances known, researched and used by dermatologists. We monitored the stability over time of the two pharmaceutical forms by exposure to environmental factors, and we analyzed from a microbiological point of view the behavior of the two pharmaceutical forms The study showed a strong antimicrobial action of the chemical compounds on the gram-positive germs, respectively Staphylococcus aureus, leading to the conclusion of the use of active compounds from the two plants, in alternative treatments against acne.